Incentivizing Student Participation in QAS Questionnaires: An Evaluation of a Guaranteed Prize System at the University of Malaga. - Vereda-Alonso, Cristina; Cerrillo-González, María del Mar; Gómez-Lahoz, César; Villén-Guzmán, María Dolores; Vereda-Alonso, Carlos (MPDI, 2024)
This paper investigates the effects of a guaranteed prize incentive, in the form of an extra score, on student engagement in the quality assurance system (QAS) questionnaires employed for evaluating teaching performance at the University of Malaga. The incentive system aims to counteract declining participation rates and mitigate potential survey fatigue among students. Employing a comprehensive dataset spanning multiple academic years and subjects, the study utilized statistical analyses to evaluate the incentive’s effectiveness, considering its potential impact on both final grades and QAS questionnaire outcomes. The results demonstrate a substantial increase in participation rates, with over 85% of students acknowledging the motivating influence of the incentive. However, concerns regarding the compromise of anonymity arose among 40% of students, possibly linked to the physical presence of teachers during the verification process of the QAS questionnaire submission. The statistical analyses raise questions about the incentive’s influence on students’ final grades while indicating that the incentive system does not significantly affect the results of the QAS questionnaires. The study contributes valuable insights into the complexities of incentivizing student participation in teaching assessments within the higher education landscape. To the best of our knowledge, there are few publications that investigate the use of an additional score as an incentive for students’ participation in QAS questionnaires.
Keywords: Profesores de universidad - Evaluación; Encuestas - Metodología; Estudiantes universitarios; Incentive system; Quality assessment surveys; Survey fatigue; Student participation